廃棄物埋立場浸出液の集水効果について - 山崎, 惟義; 田中, 信寿; 大西, 和栄; 花嶋, 正孝 (PROCEEDINGS OF ENVIRONMENTAL AND SANITARY ENGINEERING RESEARCH, 1983)
To ascertain the phenomenon by which leachate is collected by a leachate collection pipe, and how much part of leachate flows into the ground and how much is collected by the colletion pipe, (1) we experimented the leachate collection in the experimental sanitary landfill model, and (2) we analyzed seepage flow near the interface between base ground and waste. We got the results: Some part of leachate flows into the ground and the other part of it is collected by the collection pipe.(2) The amount of the leachte that flows into the ground depends only on the seepage characteristics of ground soil and rain fall intensity ie, the excess of the rain fall over seepage capacity of ground soil is collected by the collection pipe.(3) The amouns of leachate that is collected and flows into the ground are affected by the atmospheric pressure.